2012
DOI: 10.1016/j.spinee.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel sham cervical manipulation procedure

Abstract: Background Context No clinical trial of spinal manipulation for chronic neck pain, either for single or multiple intervention session(s), has employed an effective sham-manipulation control group. Purpose Validate a practical sham cervical high velocity, low amplitude (HVLA) spinal manipulation. Study design/Setting Randomized, experimental validation study in an institutional clinical research laboratory Patient Sample Eligible subjects were males and females, 18–60 years of age with mechanical neck pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 43 publications
0
33
0
1
Order By: Relevance
“…A systematic review showed that sham-controlled trials of CSM are feasible; also, they demonstrate that CSM is associated with a sizeable placebo effect, which arguably creates the necessity to test CSM with sham-controlled clinical trials, particularly if the research question is aimed at identifying specific therapeutic effects. (6) When Vernon et al (21) validated SMPCS, they analyzed that more patients reported improvement in pain following the real manipulation than the sham manipulation (38% vs 28% in the sham group) with the same sham procedure used in this study, but with no statistically significant intergroup differences in pain, pain threshold or range of motion.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…A systematic review showed that sham-controlled trials of CSM are feasible; also, they demonstrate that CSM is associated with a sizeable placebo effect, which arguably creates the necessity to test CSM with sham-controlled clinical trials, particularly if the research question is aimed at identifying specific therapeutic effects. (6) When Vernon et al (21) validated SMPCS, they analyzed that more patients reported improvement in pain following the real manipulation than the sham manipulation (38% vs 28% in the sham group) with the same sham procedure used in this study, but with no statistically significant intergroup differences in pain, pain threshold or range of motion.…”
Section: Discussionmentioning
confidence: 85%
“…To our knowledge, this study was the first to compare the treatment outcomes among that type of CSM (19,20) and a validated cervical manipulative sham procedure (14,21) using the NDI to evaluate patients with chronic neck pain. A systematic review showed that sham-controlled trials of CSM are feasible; also, they demonstrate that CSM is associated with a sizeable placebo effect, which arguably creates the necessity to test CSM with sham-controlled clinical trials, particularly if the research question is aimed at identifying specific therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations